Characterizing Wheat Rhizosphere Bacterial Microbiome Dynamics Under Salinity Stress: Insights from 16S rRNA Metagenomics for Enhancing Stress Tolerance - Mahmoud, Nourhan Fouad; M. El-Zayat, Emad; Amr, Dina; A. El-Khishin, Dina; M. Abd-Elhalim, Haytham; Hafez, Amr; Radwan, Khaled; Hamwieh, Aladdin; Tadesse, Wuletaw (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Salinity is one of the most important abiotic stress factors affecting wheat production. Salt in the soil is a major environmental stressor that can affect the bacterial community in the rhizosphere of wheat. The bacteria in the plant’s rhizosphere promote growth and stress tolerance, which vary by variety and location. Nevertheless, the soil harbors some of the most diverse microbial communities, while the rhizosphere selectively recruits according to the needs of plants in a complex harmonic regulation. The microbial composition and diversity under normal and saline conditions were assessed by comparing the rhizosphere of wheat with soil using 16S rRNA gene amplicon sequencing, highlighting the number of operational taxonomic units (OTUs). Taxonomic analyzes showed that the bacterial community was predominantly and characteristically composed of the phyla Proteobacteria, Actinobacteria, Bacteroidetes, Firmicutes, Verrucomicrobia, and Fibrobacteres, representing the usual microbial profile for the rhizosphere of wheat. Idiomarinaceae, Rheinheimera, Halomonas, and Pseudomonas (a strain of Proteobacteria), together with Gracilibacillus (a strain of Firmicutes Bacilli), were recognized as microbial signatures for the rhizosphere microbiome under saline conditions. This was observed even with unchanged soil type and genotype. These patterns occurred despite the same soil type and genotype, with salinity being the only variable. The collective action of these bacterial phyla in the rhizosphere not only improves nutrient availability but also induces systemic resistance in the plants. This synergistic effect improves plant resistance to salt stress and supports the development of salt-tolerant wheat varieties. These microbial signatures could improve our understanding of plant–microbe interactions and support the development of microbiome-based solutions for salt stress.